Joining 3YSZ Electrolyte to AISI 441 Interconnect Using the Ag Particle Interlayer: Enhanced Mechanical and Aging Properties - Xiaoqing Si; Xiaoyang Wang; Chun Li; Tong Lin; Junlei Qi; Jian Cao (Crystals, 2021)
Reactive air brazing has been widely used in fabricating solid oxide fuel/electrolysis cell (SOFC/SOEC) stacks. However, the conventional Ag–CuO braze can lead to (I) over oxidation at the steel interconnect interface caused by its adverse reactions with the CuO and (II) many voids caused by the hydrogen-induced decomposition of CuO. The present work demonstrates that the Ag particle interlayer can be used to join yttria-stabilized zirconia (YSZ) electrolytes to AISI 441 interconnect in air instead of Ag–CuO braze. Reliable joining between YSZ and AISI 441 can be realized at 920 °C. A dense and thin oxide layer (~2 μm) is formed at the AISI 441 interface. Additionally, an interatomic joining at the YSZ/Ag interface was observed by TEM. Obtained joints displayed a shear strength of ~86.1 MPa, 161% higher than that of the joints brazed by Ag–CuO braze (~33 MPa). After aging in reducing and oxidizing atmospheres (800 °C/300 h), joints remained tight and dense, indicating a better aging performance. This technique eliminates the CuO-induced issues, which may extend lifetimes for SOFC/SOEC stacks and other ceramic/metal joining applications.